Evaluation of Seed Germination of Chironji (Buchanania cochinchinensis (Lour.) M. R. Almedia) under Nursery Conditions - Malakar, Ayushman; Kumar, Rikesh; Mishra, Yogeshwar; Sinha, Animesh (International Journal of Economic Plants, 2024)
The study was carried out during the month of June to August in the year, 2022 in the FGR field in the nursery of Institute of Forest Productivity (IFP), Lalgutwa, Ranchi, Jharkhand (835303), India to find out effective germination techniques to expedite nursery propagation of Chironji, an economically significant non-timber forest produce (NTFP) in red and lateritic zone (RLZ) of eastern India. The research evaluated seven pre-treatments to enhance germination potential using seeds harvested from a Candidate Plus Tree (CPT) in the natural forest of Burdwan Forest Division, West Bengal. The study employed a completely randomized design with four replications, evaluating various germination parameters over a 50-day period. The combination of hot water treatment and mechanical scarification (T6) exhibited highest germination of 87.5% and also outperformed all other pre-treatments in every germination parameter evaluated. It also yielded the highest seed vigour indices (SVI) of 1303.53 (SVI-I) and 109.155 (SVI-II). This method proved to be the most effective for breaking seed dormancy and promoting robust seedling development of Chironji for the prevailing agroclimatic conditions in RLZ of eastern India. The outcomes of this study demonstrate an affordable and swift seed treatment method without relying on costly growth hormones or chemicals contributing to conservation efforts. Given the challenges of seed dormancy in this species, marginal farmers and state forest departments (SFDs) can employ the pre-treatment reported in the study for commercial cultivation of Chironji as well as contributing to conservation efforts of the species.